Psychometric properties of the behavioral pediatrics feeding assessment scale for children with cerebral palsy: Behavioral Pediatrics Feeding Asessment Scale - Park, Eun-Young (Progress in Nutrition, 2023)
This study aimed to investigate the Behavioral Pediatrics Feeding Assessment Scale (BPFAS) as a tool for measuring the feeding difficulty of children with cerebral palsy (CP). It was adapted using the standard adaptation process. A survey was conducted with 87 mothers of 2–8 year old children with CP. Rasch analysis was used to identify the BPFAS’s psychometric characteristics. The degree of item fit, item difficulty, rating scale analysis, and reliability were investigated. The analysis showed that the fitness index of one of the 25 items did not meet the criteria. The most difficult item was “Has required supplemental tube feeds to maintain proper nutritional status,” and the least difficult was “Takes longer than 20 min to finish a meal.” The rating scale analysis indicated that the fitness index was appropriate for the five-point scale, and the participants’ average ability estimate increased as the score rose. The reliability analysis showed that the person separation index was 3.45 and the item separation index was 3.06, indicating a reliable level. The BPFAS’s psychometric properties suggest that it is useful for measuring the feeding difficulty of children with CP. Future research should determine the reliability and validity of various aspects of the scale.